Unions and Tangible Investments: A Review and New Evidence in France - Doucouliagos, Hristos; Laroche, Patrice (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2003)
SummaryA number of conflicting theoretical hypotheses have been advanced regarding the impact of unions on investment behaviour. The net impact of unions on investment is thus an empirical issue. In this article, the available empirical literature is reviewed. In addition, new evidence of the impact of unions on investment is presented using French data. In contrast to previous studies, both aggregate and disaggregate measures of union activity are used. The results indicate that French unions, in general, have not had a negative impact on investment behaviour. However, there is some evidence that the more militant unions have a negative impact on investment.